Knowledge, Attitudes, and Practices of the Tug-Back Technique: A Cross-Sectional Survey in Endodontics - Ben Hakoma, Mohamed; Mohamed Jedeh; Khaled Elhenshiri (AlQalam Journal of Medical and Applied Sciences, 2024)
This study aimed to assess the knowledge, attitudes, practices, and challenges faced by dental practitioners regarding the tug-back technique in endodontics, a method used to ensure an effective apical seal during root canal therapy. A structured cross-sectional survey was conducted among 154 dental practitioners, including general dentists and endodontic specialists. The questionnaire comprised sections on demographic information, knowledge and attitudes toward the tug-back technique, and current practices and challenges. Data were analyzed using descriptive statistics and Fisher’s Exact Test to evaluate associations between practitioner demographics and aspects of the tug-back technique. The survey achieved a response rate of 60%, with the majority of respondents being female (77.3%) and early-career practitioners (66.9% had less than five years of experience). Most participants were familiar with the tug-back technique (57.1% reported being very familiar) and considered it essential for achieving a hermetic apical seal. Commonly used methods for confirming tug-back included tactile feedback (68.8%) and radiographic verification (63.6%). Key challenges included difficulty distinguishing between true and false tug-back and inadequate canal shaping. Fisher’s Exact Test revealed a significant association between practice type and confidence in distinguishing true versus false tug-back (p = 0.0108), suggesting higher confidence levels among specialists and academic practitioners. However, no significant association was found between years of experience and the choice of method or tool used to confirm tug-back (p = 0.9019). The findings highlight a need for targeted training in distinguishing true versus false tug-back, particularly for practitioners in general practice settings. Enhanced access to advanced diagnostic tools and hands-on workshops could help bridge knowledge gaps and improve clinical outcomes. Future research should explore the impact of training interventions on practitioners’ proficiency in using the tug-back technique and achieving effective apical seals. هدفت هذه الدراسة إلى تقييم المعرفة والمواقف والممارسات والتحديات التي يواجهها أطباء الأسنان فيما يتعلق بتقنية السحب في علاج جذور الأسنان، وهي طريقة تُستخدم لضمان إحكام الإغلاق القمي أثناء العلاج. تم إجراء دراسة مسحية مقطعية شملت 154 طبيب أسنان، بما في ذلك أطباء الأسنان العامين وأخصائيي علاج جذور الأسنان. تضمنت الاستبيان أقسامًا عن المعلومات الديموغرافية والمعرفة والمواقف تجاه تقنية السحب، بالإضافة إلى الممارسات الحالية والتحديات. تم تحليل البيانات باستخدام الإحصائيات الوصفية واختبار فيشر لتقييم العلاقات بين الخصائص الديموغرافية للممارسين والجوانب المتعلقة بتقنية السحب. بلغت نسبة الاستجابة للمسح 60%، وكان معظم المشاركين من الإناث (77.3%) ومن الممارسين في بداية حياتهم المهنية (66.9% لديهم أقل من خمس سنوات من الخبرة). أظهر معظم المشاركين دراية بتقنية السحب (57.1% أشاروا إلى أنهم على دراية كبيرة بها) واعتبروها ضرورية لضمان إحكام الإغلاق القمي. تضمنت الطرق المستخدمة بشكل شائع لتأكيد السحب التغذية الراجعة اللمسية (68.8%) والتحقق الإشعاعي (63.6%). تضمنت التحديات الرئيسية صعوبة التمييز بين السحب الحقيقي والخاطئ وشكل القناة غير المناسب. أظهر اختبار فيشر وجود علاقة ذات دلالة إحصائية بين نوع الممارسة ومستوى الثقة في التمييز بين السحب الحقيقي والخاطئ (p = 0.0108)، مما يشير إلى مستويات ثقة أعلى بين الأخصائيين والممارسين الأكاديميين. ومع ذلك، لم يتم العثور على علاقة ذات دلالة إحصائية بين سنوات الخبرة واختيار الطريقة أو الأداة المستخدمة لتأكيد السحب (p = 0.9019). تسلط النتائج الضوء على الحاجة إلى تدريب مستهدف للتمييز بين السحب الحقيقي والخاطئ، خاصةً للممارسين في البيئات العامة. يمكن أن يساعد تحسين الوصول إلى الأدوات التشخيصية المتقدمة وورش العمل العملية في سد فجوات المعرفة وتحسين النتائج السريرية. يجب أن تستكشف الأبحاث المستقبلية تأثير التدخلات التدريبية على كفاءة الممارسين في استخدام تقنية السحب وتحقيق الإغلاق القمي الفعال